Piezoelectric ceramic surface metallization method
By using magnetron sputtering technology to form a nickel-copper alloy and silver layer on the surface of piezoelectric ceramics, and adding materials such as ferrite and LaAlO3 to optimize the ceramic structure, the problem of insufficient firmness of the metallized layer in the prior art was solved, significantly Improves the electrical performance and service life of the device.
Patent Information
- Application Number
- CN202411809392.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-12-10
AI Technical Summary
In the existing piezoelectric ceramic surface metallization process, the firmness of the metallization layer is poor, which affects the electrical performance and service life of the device.
Magneto-controlled sputtering technology is used to form a nickel-copper alloy layer and a silver layer on the surface of the composite ceramic sheet. By adding ferrite and LaAlO3 to the casting slurry, the crystal structure and electrical characteristics of the ceramic are optimized and the metallization layer is improved. Combination strength with ceramics.
The piezoelectric properties of piezoelectric ceramics and the bonding strength between the metallized layer and the ceramics are significantly improved, and the electrical properties and service life of the device are improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic metallization, in particular to a piezoelectric ceramic surface metallization method. Background Art
[0002] With the rapid development of electronic information technology, piezoelectric ceramic frequency devices have been widely used in audio and video, communications, computer peripherals and other fields. According to statistics, filters and resonators made of piezoelectric ceramics are the two most widely used types of piezoelectric products in civilian electronic products. Piezoelectric ceramic frequency devices are made by performing surface metallization treatment on piezoelectric ceramic substrates and then undergoing multiple processes such as polarization. Among them, the surface metallization of piezoelectric ceramic substrates, that is, preparing a metal electrode layer on the surface of the substrate, is a key process in the production of piezoelectric ceramic frequency devices. The quality of the metal electrode layer will directly affect the device's electrical performance, stability of use, service life, and the pass rate during the processing and manufacturing process.
[0003] At present, the process of metallization treatment of piezoelectric ceramic surface is based on screen printing or vacuum coating. The screen printing method is to directly print the silver electrode slurry on the surface of the piezoelectric ceramic substrate by screen printing, and then prepare it into a metallization layer through processes such as drying and silver burning. The vacuum coating method is a physical process in which the required metal block is placed in the sagger of the vacuum coating machine, and the metal is heated and melted by electricity in the sagger, and then evaporated. After contacting the piezoelectric ceramic substrate, it is deposited on the surface of the substrate to form a metallization layer. However, due to the difference in the properties of piezoelectric ceramics and metals, the screen printing method or vacuum coating method has certain defects, and the firmness of the prepared metallization layer is poor. Summary of the invention
[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a method for metallizing the surface of piezoelectric ceramics.
[0005] The technical solutions adopted are as follows: A piezoelectric ceramic surface metallization method, as follows: S1: Prepare piezoelectric ceramic blanks; S2: preparing a tape casting slurry containing ferrite, passing the tape casting slurry through a tape casting machine to obtain a tape casting sheet, laminating the tape casting sheet with a piezoelectric ceramic body and isostatically pressing to obtain a green body; S3: After heating the green blank for degreasing in one stage, heating it to 950-1050°C in two stages and sintering it for 1-5h to obtain a composite ceramic sheet; S4: Finally, a nickel-copper alloy layer and a silver layer are formed on the surface of the composite ceramic sheet by magnetron sputtering; The structural formula of the ferrite is MFe 2 O 4 ; Where M is any one of Cu, Zn, Ni, and Co; The casting slurry comprises the following components in parts by weight: 30-50 parts of ferrite, 5-10 parts of polyvinyl butyral, 1-2 parts of polyethylene glycol 400, 1-2 parts of butyl benzyl phthalate, 1-3 parts of triolein, 20-30 parts of ethanol, and 20-30 parts of ethyl acetate.
[0006] Furthermore, the chemical structure formula of the piezoelectric ceramic is as follows: [(Na 1 / 2 K 1 / 2 ) 1-x Li x ][Nb 1-y (W 1 / 2 Ce 1 / 2 ) y ]O 3 -zwt%LaAlO 3 -uwt%Fe 2 O 3 Among them, 0<x≤0.1, 0<y≤0.1; 1≤z≤5, 1≤u≤5.
[0007] Further, x=0.03, y=0.05.
[0008] Further, z=2, u=1.
[0009] Furthermore, the first stage heating rate is 1-5°C / min, and the second stage heating rate is 10-20°C / min.
[0010] Further, sintering is carried out under a microwave environment.
[0011] Furthermore, the mass ratio of nickel to copper in the nickel-copper alloy layer is 1-9:1-9.
[0012] Furthermore, the thickness of the nickel-copper alloy layer is 0.5-1 μm, and the thickness of the silver layer is 0.1-0.5 μm.
[0013] Beneficial effects of the present invention: The present invention provides a method for metallizing the surface of piezoelectric ceramics. Doping Li at the A position of KNN ceramics can cause changes in the crystal structure. By controlling the doping amount of Li, the orthorhombic phase and the tetragonal phase coexist, thereby optimizing the performance of the piezoelectric ceramics. The electronegativity of the doped Li at the B position of KNN ceramics is stronger than that of Nb. 5+ of (W 1 / 2 Ce 1 / 2 ) 5+Composite ions can maintain the B-site electron conservation state, making the crystal structure of the ceramic denser and producing lattice distortion, which plays a positive role in improving the piezoelectric performance. 3 It has a perovskite structure and can form a multinary solid solution with a quasi-isotropic phase boundary with KNN ceramics. Near the quasi-isotropic phase boundary components, under the action of an external electric field or stress, the spontaneous polarization becomes easier to change direction, and the piezoelectric performance will be greatly improved. The properties of ferrite are between ceramics and metals, with certain conductivity and unique magnetic and electrical properties. Using it as a transition layer can effectively promote the bonding between piezoelectric ceramics and metallization layer materials, and effectively alleviate the thermal stress caused by the large difference in expansion coefficients of the two materials near the interface, thereby improving the bonding strength between the metallization layer and the piezoelectric ceramic. At present, there are no reports on using ferrite as a ceramic metallization transition layer. DETAILED DESCRIPTION
[0014] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0015] Embodiment 1: This embodiment provides a piezoelectric ceramic surface metallization method: According to the general formula [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ][Nb 0.95 (W 1 / 2 Ce 1 / 2 ) 0.05 ]O 3 -2wt%LaAlO 3 -1wt%Fe 2 O 3 stoichiometric ratio in weigh Na 2 CO 3 , K 2 CO 3 , Li 2 CO 3 , Nb 2 O 5 , WO 3 、CeO 2 , LaAlO 3 , Fe 2 O 3Add it to a ball mill, use anhydrous ethanol as a ball milling medium, mix and ball mill in a planetary ball mill for 10 hours, dry in an oven, and then pre-sinter at 800°C for 2 hours to obtain a prefabricated powder, add the prefabricated powder to a ball mill, use anhydrous ethanol as a ball milling medium, mix and ball mill again in a planetary ball mill for 10 hours, and then dry in an oven, add a polyvinyl alcohol aqueous solution with a mass concentration of 8wt% as a binder and granulate, add the obtained granules after passing through an 80-mesh screen into a mold, and press at 100MPa to obtain a piezoelectric ceramic body; Ferrite NiFe 2 O 4 40 parts by weight of 1,2-dimethoxy-2-nitropropene, 8 parts by weight of polyvinyl butyral, 1 part by weight of polyethylene glycol 400, 1 part by weight of butyl benzyl phthalate, 2 parts by weight of triolein, 30 parts by weight of ethanol and 30 parts by weight of ethyl acetate are added into a ball mill, mixed and ball-milled in a planetary ball mill for 5 hours to obtain a casting slurry, the casting slurry is passed through a casting machine to obtain a casting sheet with a thickness of 10 μm, two casting sheets and a piezoelectric ceramic body are laminated and isostatically pressed at 100 MPa in a "sandwich" structure to obtain a green blank; The green blank was placed in a microwave sintering furnace and heated to 600°C at a speed of 1°C / min for 2 hours for degreasing. Then, the microwave was turned on and heated to 1050°C at a speed of 10°C / min for 3 hours to obtain a composite ceramic sheet. The frequency and power of the microwave sintering furnace were 2.45 GHz and 1.1 kW respectively. Finally, a nickel-copper alloy layer with a thickness of 0.5 μm and a silver layer with a thickness of 0.2 μm were formed on the upper and lower surfaces of the composite ceramic sheet by magnetron sputtering. The magnetron sputtering used a nickel-copper alloy target and a pure silver target with a mass ratio of 1:1. When the vacuum degree of the sputtering studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering nickel-copper alloy target is 7A, the time is 13 min, the current when sputtering pure silver target is 7A, the time is 6 min, after the single-sided sputtering is completed, the loading fixture is automatically turned over, and the nickel-copper layer and silver layer are sputtered on the other side with the same sputtering conditions.
[0016] The tensile strength of the silver layer was measured to be 25.6 MPa according to the method in 4.5.19 of GJB 3522A-2011.
[0017] Embodiment 2: This embodiment provides a piezoelectric ceramic surface metallization method: According to the general formula [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ][Nb 0.95 (W 1 / 2 Ce1 / 2 ) 0.05 ]O 3 -2wt%LaAlO 3 -1wt%Fe 2 O 3 stoichiometric ratio in weigh Na 2 CO 3 , K 2 CO 3 , Li 2 CO 3 , Nb 2 O 5 , WO 3 、CeO 2 , LaAlO 3 , Fe 2 O 3 Add it to a ball mill, use anhydrous ethanol as a ball milling medium, mix and ball mill in a planetary ball mill for 10 hours, dry in an oven, and then pre-sinter at 800°C for 2 hours to obtain a prefabricated powder, add the prefabricated powder to a ball mill, use anhydrous ethanol as a ball milling medium, mix and ball mill again in a planetary ball mill for 10 hours, and then dry in an oven, add a polyvinyl alcohol aqueous solution with a mass concentration of 8wt% as a binder and granulate, add the obtained granules after passing through an 80-mesh screen into a mold, and press at 100MPa to obtain a piezoelectric ceramic body; Ferrite NiFe 2 O 4 30 parts by weight of 1,2-dimethoxy-2-nitropropene, 5 parts by weight of polyvinyl butyral, 1 part by weight of polyethylene glycol 400, 1 part by weight of butyl benzyl phthalate, 1 part by weight of triolein, 30 parts by weight of ethanol and 30 parts by weight of ethyl acetate are added into a ball mill, mixed and ball-milled in a planetary ball mill for 5 hours to obtain a casting slurry, the casting slurry is passed through a casting machine to obtain a casting sheet with a thickness of 10 μm, two casting sheets and a piezoelectric ceramic body are laminated and isostatically pressed at 100 MPa in a "sandwich" structure to obtain a green blank; The green blank was placed in a microwave sintering furnace and heated to 600°C at a speed of 1°C / min for 2 hours for degreasing. Then, the microwave was turned on and heated to 1050°C at a speed of 10°C / min for 3 hours to obtain a composite ceramic sheet. The frequency and power of the microwave sintering furnace were 2.45 GHz and 1.1 kW respectively. Finally, a nickel-copper alloy layer with a thickness of 0.5 μm and a silver layer with a thickness of 0.2 μm were formed on the upper and lower surfaces of the composite ceramic sheet by magnetron sputtering. The magnetron sputtering used a nickel-copper alloy target and a pure silver target with a mass ratio of 1:1. When the vacuum degree of the sputtering studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1Pa, the current when sputtering nickel-copper alloy target is 7A, the time is 13 min, the current when sputtering pure silver target is 7A, the time is 6 min, after the single-sided sputtering is completed, the loading fixture is automatically turned over, and the nickel-copper layer and silver layer are sputtered on the other side with the same sputtering conditions.
[0018] The tensile strength of the silver layer was measured to be 23.3 MPa according to the method in 4.5.19 of GJB 3522A-2011.
[0019] Embodiment 3: This embodiment provides a piezoelectric ceramic surface metallization method: According to the general formula [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ][Nb 0.95 (W 1 / 2 Ce 1 / 2 ) 0.05 ]O 3 -2wt%LaAlO 3 -1wt%Fe 2 O 3 stoichiometric ratio in weigh Na 2 CO 3 , K 2 CO 3 , Li 2 CO 3 , Nb 2 O 5 , WO 3 、CeO 2 , LaAlO 3 , Fe 2 O 3 Add it to a ball mill, use anhydrous ethanol as a ball milling medium, mix and ball mill in a planetary ball mill for 10 hours, dry in an oven, and then pre-sinter at 800°C for 2 hours to obtain a prefabricated powder, add the prefabricated powder to a ball mill, use anhydrous ethanol as a ball milling medium, mix and ball mill again in a planetary ball mill for 10 hours, and then dry in an oven, add a polyvinyl alcohol aqueous solution with a mass concentration of 8wt% as a binder and granulate, add the obtained granules after passing through an 80-mesh screen into a mold, and press at 100MPa to obtain a piezoelectric ceramic body; Ferrite NiFe 2 O 430 parts by weight of 1,2-dimethoxy- ... The green blank was placed in a microwave sintering furnace and heated to 600°C at a speed of 1°C / min for 2 hours for degreasing. Then, the microwave was turned on and heated to 1050°C at a speed of 10°C / min for 3 hours to obtain a composite ceramic sheet. The frequency and power of the microwave sintering furnace were 2.45 GHz and 1.1 kW respectively. Finally, a nickel-copper alloy layer with a thickness of 0.5 μm and a silver layer with a thickness of 0.2 μm were formed on the upper and lower surfaces of the composite ceramic sheet by magnetron sputtering. The magnetron sputtering used a nickel-copper alloy target and a pure silver target with a mass ratio of 1:1. When the vacuum degree of the sputtering studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering nickel-copper alloy target is 7A, the time is 13 min, the current when sputtering pure silver target is 7A, the time is 6 min, after the single-sided sputtering is completed, the loading fixture is automatically turned over, and the nickel-copper layer and silver layer are sputtered on the other side with the same sputtering conditions.
[0020] The tensile strength of the silver layer was measured to be 22.8 MPa according to the method in 4.5.19 of GJB 3522A-2011.
[0021] Embodiment 4: This embodiment provides a piezoelectric ceramic surface metallization method: According to the general formula [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ][Nb 0.95 (W 1 / 2 Ce 1 / 2 ) 0.05 ]O 3 -2wt%LaAlO 3 -1wt%Fe 2 O 3 stoichiometric ratio in weigh Na 2 CO 3 , K 2 CO 3 , Li 2 CO 3 , Nb 2 O5 , WO 3 、CeO 2 , LaAlO 3 , Fe 2 O 3 Add it to a ball mill, use anhydrous ethanol as a ball milling medium, mix and ball mill in a planetary ball mill for 10 hours, dry in an oven, and then pre-sinter at 800°C for 2 hours to obtain a prefabricated powder, add the prefabricated powder to a ball mill, use anhydrous ethanol as a ball milling medium, mix and ball mill again in a planetary ball mill for 10 hours, and then dry in an oven, add a polyvinyl alcohol aqueous solution with a mass concentration of 8wt% as a binder and granulate, add the obtained granules after passing through an 80-mesh screen into a mold, and press at 100MPa to obtain a piezoelectric ceramic body; Ferrite CuFe 2 O 4 40 parts by weight of 1,2-dimethoxy-2-nitropropene, 8 parts by weight of polyvinyl butyral, 1 part by weight of polyethylene glycol 400, 1 part by weight of butyl benzyl phthalate, 2 parts by weight of triolein, 30 parts by weight of ethanol and 30 parts by weight of ethyl acetate are added into a ball mill, mixed and ball-milled in a planetary ball mill for 5 hours to obtain a casting slurry, the casting slurry is passed through a casting machine to obtain a casting sheet with a thickness of 10 μm, two casting sheets and a piezoelectric ceramic body are laminated and isostatically pressed at 100 MPa in a "sandwich" structure to obtain a green blank; The green blank was placed in a microwave sintering furnace and heated to 600°C at a speed of 1°C / min for 2 hours for degreasing. Then, the microwave was turned on and heated to 1050°C at a speed of 10°C / min for 3 hours to obtain a composite ceramic sheet. The frequency and power of the microwave sintering furnace were 2.45 GHz and 1.1 kW respectively. Finally, a nickel-copper alloy layer with a thickness of 0.5 μm and a silver layer with a thickness of 0.2 μm were formed on the upper and lower surfaces of the composite ceramic sheet by magnetron sputtering. The magnetron sputtering used a nickel-copper alloy target and a pure silver target with a mass ratio of 1:1. When the vacuum degree of the sputtering studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering nickel-copper alloy target is 7A, the time is 13 min, the current when sputtering pure silver target is 7A, the time is 6 min, after the single-sided sputtering is completed, the loading fixture is automatically turned over, and the nickel-copper layer and silver layer are sputtered on the other side with the same sputtering conditions.
[0022] The tensile strength of the silver layer was measured to be 20.5 MPa according to the method in 4.5.19 of GJB 3522A-2011.
[0023] Comparative Example 1: The method is basically the same as Example 1, except that it does not contain a cast sheet layer, that is, the piezoelectric ceramic body is directly sintered and then magnetron sputtered; This comparative example provides a piezoelectric ceramic surface metallization method: According to the general formula [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ][Nb 0.95 (W 1 / 2 Ce 1 / 2 ) 0.05 ]O 3 -2wt%LaAlO 3 -1wt%Fe 2 O 3 stoichiometric ratio in weigh Na 2 CO 3 , K 2 CO 3 , Li 2 CO 3 , Nb 2 O 5 , WO 3 、CeO 2 , LaAlO 3 , Fe 2 O 3 Add it to a ball mill, use anhydrous ethanol as a ball milling medium, mix and ball mill in a planetary ball mill for 10 hours, dry in an oven, and then pre-sinter at 800°C for 2 hours to obtain a prefabricated powder, add the prefabricated powder to a ball mill, use anhydrous ethanol as a ball milling medium, mix and ball mill again in a planetary ball mill for 10 hours, and then dry in an oven, add a polyvinyl alcohol aqueous solution with a mass concentration of 8wt% as a binder and granulate, add the obtained granules after passing through an 80-mesh screen into a mold, and press at 100MPa to obtain a piezoelectric ceramic body; The piezoelectric ceramic body was placed in a microwave sintering furnace and heated to 600°C at a speed of 1°C / min for 2 hours for degreasing. The microwave was then turned on and heated to 1050°C at a speed of 10°C / min for 3 hours to obtain a ceramic sheet. The frequency and power of the microwave sintering furnace were 2.45 GHz and 1.1 kW, respectively. Finally, a nickel-copper alloy layer with a thickness of 0.5 μm and a silver layer with a thickness of 0.2 μm were formed on the upper and lower surfaces of the ceramic sheet by magnetron sputtering. The magnetron sputtering used a nickel-copper alloy target and a pure silver target with a mass ratio of 1:1. When the vacuum degree of the sputtering studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1Pa, the current when sputtering nickel-copper alloy target is 7A, the time is 13 min, the current when sputtering pure silver target is 7A, the time is 6 min, after the single-sided sputtering is completed, the loading fixture is automatically turned over, and the nickel-copper layer and silver layer are sputtered on the other side with the same sputtering conditions.
[0024] The tensile strength of the silver layer was measured to be 13.2 MPa according to the method in 4.5.19 of GJB 3522A-2011.
[0025] Comparative Example 2: The same as Example 1, except that LaAlO is not added during the preparation of the piezoelectric ceramic. 3; This comparative example provides a piezoelectric ceramic surface metallization method: According to the general formula [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ][Nb 0.95 (W 1 / 2 Ce 1 / 2 ) 0.05 ]O 3 -1wt%Fe 2 O 3 stoichiometric ratio in weigh Na 2 CO 3 , K 2 CO 3 , Li 2 CO 3 , Nb 2 O 5 , WO 3 、CeO 2 , Fe 2 O 3 Add it to a ball mill, use anhydrous ethanol as a ball milling medium, mix and ball mill in a planetary ball mill for 10 hours, dry in an oven, and then pre-sinter at 800°C for 2 hours to obtain a prefabricated powder, add the prefabricated powder to a ball mill, use anhydrous ethanol as a ball milling medium, mix and ball mill again in a planetary ball mill for 10 hours, and then dry in an oven, add a polyvinyl alcohol aqueous solution with a mass concentration of 8wt% as a binder and granulate, add the obtained granules after passing through an 80-mesh screen into a mold, and press at 100MPa to obtain a piezoelectric ceramic body; Ferrite NiFe 2 O 440 parts by weight of 1,2-dimethoxy-2-nitropropene, 8 parts by weight of polyvinyl butyral, 1 part by weight of polyethylene glycol 400, 1 part by weight of butyl benzyl phthalate, 2 parts by weight of triolein, 30 parts by weight of ethanol and 30 parts by weight of ethyl acetate are added into a ball mill, mixed and ball-milled in a planetary ball mill for 5 hours to obtain a casting slurry, the casting slurry is passed through a casting machine to obtain a casting sheet with a thickness of 10 μm, two casting sheets and a piezoelectric ceramic body are laminated and isostatically pressed at 100 MPa in a "sandwich" structure to obtain a green blank; The green blank was placed in a microwave sintering furnace and heated to 600°C at a speed of 1°C / min for 2 hours for degreasing. Then, the microwave was turned on and heated to 1050°C at a speed of 10°C / min for 3 hours to obtain a composite ceramic sheet. The frequency and power of the microwave sintering furnace were 2.45 GHz and 1.1 kW respectively. Finally, a nickel-copper alloy layer with a thickness of 0.5 μm and a silver layer with a thickness of 0.2 μm were formed on the upper and lower surfaces of the composite ceramic sheet by magnetron sputtering. The magnetron sputtering used a nickel-copper alloy target and a pure silver target with a mass ratio of 1:1. When the vacuum degree of the sputtering studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering nickel-copper alloy target is 7A, the time is 13 min, the current when sputtering pure silver target is 7A, the time is 6 min, after the single-sided sputtering is completed, the loading fixture is automatically turned over, and the nickel-copper layer and silver layer are sputtered on the other side with the same sputtering conditions.
[0026] The tensile strength of the silver layer was measured to be 20.6 MPa according to the method in 4.5.19 of GJB 3522A-2011.
[0027] Comparative Example 3: The same as Example 1, except that Fe is not added during the preparation of the piezoelectric ceramic. 2 O 3; This embodiment provides a piezoelectric ceramic surface metallization method: According to the general formula [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ][Nb 0.95 (W 1 / 2 Ce 1 / 2 ) 0.05 ]O 3 -2wt%LaAlO 3 Weigh Na in the stoichiometric ratio 2 CO 3 , K 2 CO 3 , Li 2 CO3 , Nb 2 O 5 , WO 3 、CeO 2 , LaAlO 3 Add it to a ball mill, use anhydrous ethanol as a ball milling medium, mix and ball mill in a planetary ball mill for 10 hours, dry in an oven, and then pre-sinter at 800°C for 2 hours to obtain a prefabricated powder, add the prefabricated powder to a ball mill, use anhydrous ethanol as a ball milling medium, mix and ball mill again in a planetary ball mill for 10 hours, and then dry in an oven, add a polyvinyl alcohol aqueous solution with a mass concentration of 8wt% as a binder and granulate, add the obtained granules after passing through an 80-mesh screen into a mold, and press at 100MPa to obtain a piezoelectric ceramic body; Ferrite NiFe 2 O 4 40 parts by weight of 1,2-dimethoxy-2-nitropropene, 8 parts by weight of polyvinyl butyral, 1 part by weight of polyethylene glycol 400, 1 part by weight of butyl benzyl phthalate, 2 parts by weight of triolein, 30 parts by weight of ethanol and 30 parts by weight of ethyl acetate are added into a ball mill, mixed and ball-milled in a planetary ball mill for 5 hours to obtain a casting slurry, the casting slurry is passed through a casting machine to obtain a casting sheet with a thickness of 10 μm, two casting sheets and a piezoelectric ceramic body are laminated and isostatically pressed at 100 MPa in a "sandwich" structure to obtain a green blank; The green blank was placed in a microwave sintering furnace and heated to 600°C at a speed of 1°C / min for 2 hours for degreasing. Then, the microwave was turned on and heated to 1050°C at a speed of 10°C / min for 3 hours to obtain a composite ceramic sheet. The frequency and power of the microwave sintering furnace were 2.45 GHz and 1.1 kW respectively. Finally, a nickel-copper alloy layer with a thickness of 0.5 μm and a silver layer with a thickness of 0.2 μm were formed on the upper and lower surfaces of the composite ceramic sheet by magnetron sputtering. The magnetron sputtering used a nickel-copper alloy target and a pure silver target with a mass ratio of 1:1. When the vacuum degree of the sputtering studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering nickel-copper alloy target is 7A, the time is 13 min, the current when sputtering pure silver target is 7A, the time is 6 min, after the single-sided sputtering is completed, the loading fixture is automatically turned over, and the nickel-copper layer and silver layer are sputtered on the other side with the same sputtering conditions.
[0028] The tensile strength of the silver layer was measured to be 18.4 MPa according to the method in 4.5.19 of GJB 3522A-2011.
[0029] Comparative Example 4: The same as Example 1, except that [(Na 1 / 2 K1 / 2 ) 0.97 Li 0.03 ]NbO 3 Instead of [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ][Nb 0.95 (W 1 / 2 Ce 1 / 2 ) 0.05 ]O 3; This embodiment provides a piezoelectric ceramic surface metallization method: According to the general formula [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ]NbO 3 -2wt%LaAlO 3 -1wt%Fe 2 O 3 Weigh Na in the stoichiometric ratio 2 CO 3 , K 2 CO 3 , Li 2 CO 3 , Nb 2 O 5 Add it to a ball mill, use anhydrous ethanol as a ball milling medium, mix and ball mill in a planetary ball mill for 10 hours, dry in an oven, and then pre-sinter at 800°C for 2 hours to obtain a prefabricated powder, add the prefabricated powder to a ball mill, use anhydrous ethanol as a ball milling medium, mix and ball mill again in a planetary ball mill for 10 hours, and then dry in an oven, add a polyvinyl alcohol aqueous solution with a mass concentration of 8wt% as a binder and granulate, add the obtained granules after passing through an 80-mesh screen into a mold, and press at 100MPa to obtain a piezoelectric ceramic body; Ferrite NiFe 2 O 4 40 parts by weight of 1,2-dimethoxy-2-nitropropene, 8 parts by weight of polyvinyl butyral, 1 part by weight of polyethylene glycol 400, 1 part by weight of butyl benzyl phthalate, 2 parts by weight of triolein, 30 parts by weight of ethanol and 30 parts by weight of ethyl acetate are added into a ball mill, mixed and ball-milled in a planetary ball mill for 5 hours to obtain a casting slurry, the casting slurry is passed through a casting machine to obtain a casting sheet with a thickness of 10 μm, two casting sheets and a piezoelectric ceramic body are laminated and isostatically pressed at 100 MPa in a "sandwich" structure to obtain a green blank; The green blank was placed in a microwave sintering furnace and heated to 600°C at a speed of 1°C / min for 2 hours for degreasing. Then, the microwave was turned on and heated to 1050°C at a speed of 10°C / min for 3 hours to obtain a composite ceramic sheet. The frequency and power of the microwave sintering furnace were 2.45 GHz and 1.1 kW respectively. Finally, a nickel-copper alloy layer with a thickness of 0.5 μm and a silver layer with a thickness of 0.2 μm were formed on the upper and lower surfaces of the composite ceramic sheet by magnetron sputtering. The magnetron sputtering used a nickel-copper alloy target and a pure silver target with a mass ratio of 1:1. When the vacuum degree of the sputtering studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering nickel-copper alloy target is 7A, the time is 13 min, the current when sputtering pure silver target is 7A, the time is 6 min, after the single-sided sputtering is completed, the loading fixture is automatically turned over, and the nickel-copper layer and silver layer are sputtered on the other side with the same sputtering conditions.
[0030] The tensile strength of the silver layer was measured to be 24.6 MPa according to the method in 4.5.19 of GJB 3522A-2011.
[0031] Performance Test: The surfaces of the piezoelectric ceramics after surface metallization in Examples 1-4 and Comparative Examples 2-4 were polished, polarized for 20 minutes at a DC voltage of 4 kV / mm in silicone oil at 120° C., and then placed for 24 hours as samples to test their performance.
[0032] The room temperature piezoelectric constant of the sample was measured using a ZJ-3AN quasi-static piezoelectric constant tester. d 33 ; The electromechanical coupling coefficient kp, mechanical quality factor Qm and dielectric loss tanδ (25°C, 1V, 1kHz) of the samples were measured and analyzed using a precision impedance analyzer (Agilent HP4294A). The test results are shown in Table 1 below: ; As can be seen from Table 1 above, the piezoelectric ceramics of the present invention have excellent piezoelectric properties; From the comparison between Example 1 and Comparative Examples 2 and 3, it can be seen that LaAlO 3 and Fe 2 O 3 The addition plays a positive role in improving the piezoelectric performance of piezoelectric ceramics; From the comparison between Example 1 and Comparative Example 4, we can see that (W 1 / 2 Ce 1 / 2 ) 5+Doping can maintain the B-site electron conservation state and replace the B-site element Nb, which plays a positive role in improving the piezoelectric properties of piezoelectric ceramics.
[0033] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for metallizing the surface of a piezoelectric ceramic, characterized in that: The details are as follows: S1: preparing a piezoelectric ceramic body; S2: preparing a tape casting slurry containing ferrite, passing the tape casting slurry through a tape casting machine to obtain a tape casting sheet, laminating the tape casting sheet with a piezoelectric ceramic body and isostatically pressing to obtain a green body; S3: After heating the green blank for degreasing in one stage, heating it to 950-1050°C in two stages and sintering it for 1-5h to obtain a composite ceramic sheet; S4: Finally, a nickel-copper alloy layer and a silver layer are formed on the surface of the composite ceramic sheet by magnetron sputtering; The structural formula of the ferrite is MFe2O4; Wherein M is any one of Cu, Zn, Ni and Co; The casting slurry comprises the following components in parts by weight: 30-50 parts of ferrite, 5-10 parts of polyvinyl butyral, 1-2 parts of polyethylene glycol 400, 1-2 parts of butyl benzyl phthalate, 1-3 parts of triolein, 20-30 parts of ethanol, and 20-30 parts of ethyl acetate.
2. The piezoelectric ceramic surface metallization method according to claim 1, characterized in that: The general chemical structure formula of the piezoelectric ceramic is as follows: <h2 style=";text-align:left;direction:ltr">[(Na<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> K<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Li<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> ][Nb<h2 style=";text-align:left;direction:ltr"> 1-y <h2 style=";text-align:left;direction:ltr"> (W<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> Ce<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> ]O3-zwt%LaAlO3-uwt%Fe2O3 Among them, 0<x≤0.1, 0<y≤0.1; 1≤z≤5, 1≤u≤5.
3. The method for metallizing the surface of piezoelectric ceramics according to claim 2, characterized in that: x=0.03,y=0.
05.
4. The method for metallizing the surface of piezoelectric ceramics according to claim 2, characterized in that: z=2,u=1.
5. The method for metallizing the surface of piezoelectric ceramics according to claim 1, characterized in that: The heating rate of the first stage is 1-5℃ / min, and the heating rate of the second stage is 10-20℃ / min.
6. The method for metallizing the surface of piezoelectric ceramics according to claim 1, characterized in that: The sintering was carried out in a microwave environment.
7. The method for metallizing the surface of piezoelectric ceramics according to claim 1, characterized in that: The mass ratio of nickel to copper in the nickel-copper alloy layer is 1-9:1-9.
8. The method for metallizing the surface of piezoelectric ceramics according to claim 1, characterized in that: The thickness of the nickel-copper alloy layer is 0.5-1 μm, and the thickness of the silver layer is 0.1-0.5 μm.
Citation Information
Patent Citations
Method for improving ceramic surface metalized film adhesive force
CN108675834A
Method of metallizing ferrite ceramics and component comprising metallized ferrite ceramic
CN110114326A
Multilayer lead-free piezoelectric ceramic as well as preparation method and application thereof
CN116063076A
Composite ceramic / metal core-shell microballoon and its prepn
CN1772707A
Ceramic-polymer, ceramic-ceramic or ceramic-metal composite, e.g. a piezoceramic-polymer composite for an ultrasonic transducer
DE19814018A1